Hypermagnesemia and Dilated Cardiomyopathy in a 10-year-old Male Patient on Hemodialysis, A Case Report - Akhavansepahi, Mohsen; Hoseini, Rozita (Journal of Pediatric Nephrology, 2019)
A combination of hypermagnesemia, dilated cardiomyopathy, hypertension, and chronic renal frailer is a rare presentation in children. One of important and rare side effects of chronic renal frailer is hypermagnesemia. In this article, we discuss the association between hypermagnesemia and cardiomyopathy and how patients with none oliguric chronic renal failure develop hypermagnesemia. A 10-year-old boy presented to our PICU ward with chief complaints of respiratory distress, lethargy, and weakness since three days ago. On physical examination, the patient had respiratory distress and was hypertensive and ill. Keywords: Hypertension; Hypermagnesemia; Cardiomyopathy.